Can convergence of agricultural sciences support innovation by resource-poor farmers in Africa? The cases of Benin and Ghana - van Huis, ARNOLD; JIGGINS, Janice; KOSSOU, KODJO DANSOU; LEEUWIS, Cees; Röling, N.; TOSSOU, COCOU RIGOBERT (My University, 2011)
The article introduces the IJAS special issue on the Convergence of Sciences (CoS) research programme that took place in Benin and Ghana between 2002 and 2006. CoS sought to develop pro-poor pathways of science. Starting initially from the assumption that science impact could be improved by developing farm technologies that are appropriate for the circumstances of resource-poor farmers, the nine researchers soon ran into the very limited windows of opportunity that the farmers face. Improving productivity at the farm level is thwarted by limited access to markets, infrastructure, inputs, credit and services, and by cheap imports. Farmers have no political clout, and agriculture is a source of rent for a host of actors including local and national governments. In these conditions, poverty reduction requires institutional change rather than participatory technology development. All nine researchers tried in their own way to deal with the institutional dimension. This special issue reports on these attempts. The introductory article provides background and context for understanding the institutional issues involved.
Keywords: Benin; Ghana; resource-poor farmers; agricultural science; institutional factors; windows of opportunity